Investigation of surface roughness of austenitic manganese steel in hot machining - Ozler, L.; Tosun, N.; Inan, A. (Scientific and Technical Research Council of Turkey, 2000)
In this study, surface roughness of austenitic manganese steel was investigated in hot machining by heating with a liquid petroleum gas flame in a lathe machine. First, the value of surface roughness was measured under cutting conditions that varied in terms of cutting speed, feed, cutting depth and heating temperature. The relationship between surface roughness and cutting conditions was determined. Later, an experimental design was made and a surface roughness equation was obtained by factorial regression analysis.
Ostenitik Manganli Celigin Sicak Talash Islenmesinde Yuzey Puruzlulugunun Incelenmesi
Keywords: Austenitic manganese steel; Hot machining; Surface roughness